A Modified Proximal Stent-Graft for Spinal Cord Preconditioning During Staged Endovascular Repair of Thoracoabdominal Aortic Aneurysms. (October 2020) - Rinaldi, Enrico; Carta, Niccolò; Melissano, Germano; Chiesa, Roberto; Bertoglio, Luca
Purpose: To describe a new custom-made thoracic device able to seal against the aortic wall and occlude intercostal arteries for spinal cord preconditioning during the first thoracic stage of a thoracoabdominal endovascular repair.Technique: The custom-made device, based on the Zenith Alpha stent-graft, combines different features from 2 previously described devices: the outer part is designed with a bell-bottom configuration similar to the "Embo" stent-graft, while the inner part mimics the "2 in 1" design. The outer stent-graft is designed to span the entire length of the thoracic aorta and cover as many intercostal arteries as possible during the first stage to effectively precondition the spinal cord. The sutured inner component is customizable in diameter and 20 to 40 mm shorter than the outer stent-graft. The technique has been used in 5 patients.Conclusion: The use of this new custom-made thoracic stent-graft might represent an additional tool for effectively preconditioning the spinal cord during fenestrated and branched staged procedures whenever a proximal thoracic proximal component is needed.